A Study on Adoption of E-Health Services : Developing an Integrated Framework in a Multinational Context - Dash, Ganesh; Akmal, Syed; Chakraborty, Debarun (Indian Journal of Marketing, 2022)
Purpose : This study focused on adopting e-health services in a global context. Researchers intended to address three primary research questions: How do the factors affect the prospective app users’ initial trust and adoption intention? Does initial trust mediate the relationship between trialability, perceived ease of use, subjective norms, and intention to adopt? Finally, how do Indian and Saudi Arabian consumers differ in their intention to adopt and the possible reasons? Methodology : Four hundred twenty-six potential e-health services users from Saudi Arabia and India were considered as the sample. Structural equation modeling was used to analyze the same. Further, a multi-group analysis was undertaken to compare both samples. Findings : The findings suggested that trialability (TB) had a positive and significant impact on both initial trust (IT) and intention to adopt (IA). Perceived ease of use (PEOU) had a significant and positive impact on IA; however, it was not valid for IT. Subjective norms (SN) positively and significantly impacted IT and IA. Further, IT substantially affected IA. The multi-group analysis found that in the case of India, TB had a significant and positive impact on both IT and IA. In contrast, it did not positively impact IT in the case of Saudi Arabia. PEOU had an insignificant impact on IT for both the samples, and multi-group analysis was confirmed. For both samples, SN had a significant and positive impact on IT. IT had a significant and positive impact on IA for both samples. Finally, IT was a good mediator between TB and SN with IA. Originality : This study provided a unique futuristic e-health adoption framework tested in a multinational and emerging economy context. It combined four major theories in doing the same.